Seeing the baby, doing family: commercial ultrasound as family practice? - Roberts, Julie; Griffiths, Frances; Verran, Alice (Sage, 2017)
Medical sociologists and anthropologists have studied the social significance of obstetric ultrasound for families but little is known about how women and families make use of commercially available ultrasound scans. This article draws on interviews with women who booked a scan with a commercial company in the UK. For some women, commercial ultrasound can be understood as a family practice. We investigate this theme by examining who accompanies women to commercial scan appointments, how scan images are shared and how sonograms are used as prompts to resemblance talk. We argue that commercial scans are more than an additional opportunity to acquire ‘baby’s first picture’ and offer a flexible resource to do family, creating and affirming family relationships and rehearsing roles as parents, siblings and grandparents. Our findings confirm the importance of imagination in doing family and raise questions about the role of technology and commercial interests in shaping family practices.